Kelayakan Masker Daun Pegagan (Centella Asiatica) Sebagai Perawatan Kulit Wajah Menua (Anti Aging) - Diana Gusmiati; Hayatunnufus (Jurnal Tata Rias, 2023)
This research is motivated by problems that occur in facial skin, including aging, which is caused by extrinsic and intrinsic factors. This study aims to determine the flavonoid content and feasibility of Centella asiatica leaf masks. This study employs a quantitative research method with an experimental approach, specifically pre-experimentation, to assess the feasibility of Centella asiatica leaf masks as a treatment for aging facial skin care. The object of this study is Centella asiatica leaves, which are made into a powder mask used for typical facial skin care for aging skin. Research Instrument Laboratory Test Organoleptic Test (Aroma Hedonic Test. Flavonoid content of 11,6420 ppm (0.0116%) in 100 grams of the sample. Organoleptic test texture 29% quite smooth, 71% smooth. Organoleptic test aroma: 14.5% less aromatic, 14.5% quite aromatic, and 71% aromatic. Organoleptic test: adhesive power 14% less adhesive, 14% quite adhesive, and 53% adhesive. Hedonic test 57% quite like, 43% like. The texture of the Centella Asiatica leaf mask is smooth, its aroma is distinctive, and it has quite adhesive power. It is recommended for those who have aging facial skin to use the Centella Asiatica leaf mask.